2011 IEEE 73rd Vehicular Technology Conference (VTC Spring) 2011
DOI: 10.1109/vetecs.2011.5956277
|View full text |Cite
|
Sign up to set email alerts
|

Measuring IEEE 802.11p Performance for Active Safety Applications in Cooperative Vehicular Systems

Abstract: Abstract-In this paper, we present a measurement study of application layer performance in IEEE 802.11p vehicular networks. More specifically, our focus is on active safety applications, which are based on the exchange of beacon messages containing status information between close-by vehicles. We consider two performance metrics relevant to active safety applications: the first is application-layer goodput, which can be used to optimize congestion control techniques aimed at limiting the beaconing load on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…For example, emergency signals should prevail over video downloads. In this context, the 802.11p protocol [29] makes special arrangements so that emergency critical messages can use an exclusive channel. The protocol defines seven 10MHz channels in the 5.9GHz band, and one of the channels (control channel, CCH) is exclusively used for safety applications.…”
Section: Criticalitymentioning
confidence: 99%
“…For example, emergency signals should prevail over video downloads. In this context, the 802.11p protocol [29] makes special arrangements so that emergency critical messages can use an exclusive channel. The protocol defines seven 10MHz channels in the 5.9GHz band, and one of the channels (control channel, CCH) is exclusively used for safety applications.…”
Section: Criticalitymentioning
confidence: 99%
“…In NLOS conditions the receiver gets only the reflected waves and the connection is less reliable. According to [19], the reliability of successful transmission of beacon In this paper, we confine ourselves strictly to the idealized model of V2V system; all EM transmissions are considered successful and their delays not exceeding 100 ms.…”
Section: Simple V2v System Modelmentioning
confidence: 99%
“…Comparing the braking time sequences (18) and (19) it is found that VANET system can reduce the delay of applying the brakes in a motorcade at size: Upon taking the said into account:…”
Section: Figure 2 -Motorcade On Freewaymentioning
confidence: 99%
“…The authors [15] conducted tests on the IEEE 802.11p standard with the dedicated hardware NEC Linkbird-MX. The connectivity to other devices with the Linkbird was performed only via wired Ethernet due to physical limitations of the Linkbird hardware.…”
Section: Related Workmentioning
confidence: 99%